2021
DOI: 10.3389/fmed.2021.677626
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Flexible Tip Bougie™ in Intubating Simulated Difficult Airway Model

Abstract: This prospective, randomized, cross-over study compared the performance of the novel Flexible Tip Bougie™ (FTB) with a conventional bougie as an intubation aid in a simulated difficult airway manikin model among anaesthesiology trainees with regards of first pass success rate, time to intubation, number of attempts and ease of use. Sixty-two anesthesiology trainees, novice to the usage of FTB, participated in this study. Following a video demonstration, each participant performed endotracheal intubation on a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Mahli et al demonstrated that the intubation time was significantly faster with the Flexible Tip Bougie (32.0 s) than the Portex Single-Use Introducer (41.5 s). 10 Another study conducted by Cormack et al obtained results indicating that total intubation time was significantly shorter with the Flexible Tip Bougie (37.5 s) compared to the Frova Intubating Introducer (63.0 s). 11 Additionally, the results from Evrin et al also showed that intubation time was significantly faster with the Flexible Tip Bougie (29.0 s) than a standard bougie (38.0 s).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Mahli et al demonstrated that the intubation time was significantly faster with the Flexible Tip Bougie (32.0 s) than the Portex Single-Use Introducer (41.5 s). 10 Another study conducted by Cormack et al obtained results indicating that total intubation time was significantly shorter with the Flexible Tip Bougie (37.5 s) compared to the Frova Intubating Introducer (63.0 s). 11 Additionally, the results from Evrin et al also showed that intubation time was significantly faster with the Flexible Tip Bougie (29.0 s) than a standard bougie (38.0 s).…”
Section: Resultsmentioning
confidence: 96%
“…The results remain in line with several previous studies which were in favour of the Flexible Tip Bougie compared to others in term of ease of use. [7][8][9][10][11]14 According to feedback from the participants, the Flexible Tip Bougie is easier to use because of its anterior curve of body and the flexible tip that can be directed both anteriorly and posteriorly. In the scenario of difficult airway, it is important to select the easiest to use and most familiar bougie to facilitate successful intubation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations